Pengaruh Kinerja Keuangan Terhadap Likuiditas Saham Pada Perusahaan yang Terdaftar di Index Saham Syariah Indonesia (ISSI): Pengaruh Kinerja Keuangan Terhadap Likuiditas Saham Pada Perusahaan yang Terdaftar di Index Saham Syariah Indonesia (ISSI) - mesi hera wati (IQTISHADUNA, 2020)
Abstract One of the factors that influence the stock liquidity of a company is financial performance. Stock liquidity is an interesting thing for investors to attract interest in investing in various companies. Because basically the main goal of investors investing in a company is to make a profit. The higher the level of liquidity of a stock, the easier it is to sell or buy shares in a company. This allows investors to get high profits from the results of stock liquidity. This study aims to examine the effect of financial performance on stock liquidity. The company's financial performance uses a proxy current ratio (CR), return on assets (ROA), debt equity ratio (DER) and total asset turn over. Whereas stock liquidity uses an indicator of stock trading transaction volume. The sampling method uses purposive sampling technique. The total sample of 169 companies listed on the Indonesian Sharia Stock Index (ISSI) for the period 2014-2016. Data analysis techniques use a quantitative approach. This study concluded that the variable liquidity ratio (CR) significantly influence stock liquidity with a significance value of 0.019. The profitability variable (ROA) has a significant effect on stock liquidity with a significance value of 0.049. Solvency Variable (DER) significantly influence stock liquidity with a significance value of 0.017. Activity Ratio variable has a significant effect on stock liquidity with a significance value of 0.004. Keywords: CR, ROA, DER, Activities and Stock Liquidity